PROSPECTS FOR THE DEVELOPMENT OF PRODUCTION BASED ON INTERNATIONAL STANDARDS (Web of Discoveries: Journal of Analysis and Inventions, 2026)
The article developed prospects and practical mechanisms for the development of product production in the Namangan region on the basis of international standards. The study summarized international empirical evidence (ISO 9001, ISO 14001, ISO 45001) on the impact of standard implementation on enterprise outcomes and linked to local institutional conditions. The presence of a free economic zone (“Namangan” EIZ) in the Namangan region provides additional opportunities for investment and the placement of exportbop production. As a result of the article, a “5-Step roadmap”, a support package for state and territorial institutions, a KPI at the enterprise level, and a cost–benefit (CBA) assessment model were proposed. Accordingly, the implementation of standardization with the integration of technological modernization and training of personnel was based on the fact that Namangan is a real prospect of increasing the competitiveness of exports and the domestic market.